Pengembangan Sistem Kontrol Populasi Ikan Berbasis Arduino Uno dengan Sensor Ultrasonik - Eka Kusuma Pratama; Musriatun Napiah; Sujiliani Heristian; Arina Selawati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2024)
Fish populations are one of the important assets in maintaining the balance of aquatic ecosystems. To manage fish populations effectively, an innovative and automated approach is needed. This research aims to develop an Arduino Uno-based fish population control system with ultrasonic sensors as an environmentally friendly and efficient solution. The developed system uses ultrasonic sensors to detect the presence of fish in a pond or water container. The detection data from the ultrasonic sensor is then processed by the Arduino Uno microcontroller. The system can identify the number of fish in aquatic containers and take appropriate action to control fish populations. This research integrates ultrasonic sensor technology with Arduino Uno control capabilities to provide an accurate and automated solution in controlling fish populations. In trials, this system succeeded in identifying and controlling fish populations well, maintaining the balance of aquatic ecosystems without the need for direct human intervention The results of this research have great potential in fish farming applications, environmental research, and natural resource conservation. With the proposed automated approach, it is expected to make a positive contribution in maintaining the balance of aquatic ecosystems and supporting environmental sustainability